Functional characterization of Arabidopsis thaliana Synaptotagmin1 domains using Tricalbin3 chimeras in Saccharomyces cerevisiae - Benítez-Fuente, Francisco; Amorim-Silva, Vitor; Collado, Javier; Fernández-Busnadiego, Rubén; Botella-Mesa, Miguel Ángel (My University, 2023)
Synaptotagmin1 (SYT1) is an Arabidopsis thaliana endoplasmic reticulum (ER)-plasma membrane contact site tether involved in biotic and abiotic stress resistance. These resistance roles have been related to SYT1 tethering and lipid-transport functions. However, the specific contributions of SYT1 domains to these functions and their relevance in stress resistance remain unknown. To efficiently investigate each SYT1 domain in vivo, we carried out domain interchanges in the model organism Saccharomyces cerevisiae (yeast). Tricalbin3 (Tcb3) is a SYT1 homolog in yeast, and it is essential for heat-shock tolerance. Tcb3 also mediates the formation of high-curvature peaks at the ER, which is promotes during heat, and would facilitate lipid homeostasis between the PM and the ER. We generated constructs expressing SYT1/Tcb3 chimeras tagged to fluorescent proteins, transformed them into tcb3Δ yeast cells and studied their subcellular localization and ability to complement the heat-shock hypersensitivity of tcb3Δ. We are further analyzing the ER-peak formation ability of these chimeras by cryo-electron tomography. Our work revealed that SYT1 did not show the localization pattern of Tcb3, nor could complement the heat-shock hypersensitivity of tcb3Δ. However, Tcb3 chimeras containing either SYT1 SMP or C2 domains showed a Tcb3 subcellular pattern and a heat-shock tolerance similar to that of tcb3Δ/Tcb3- GFP complemented strains. Further, Tcb3 N-terminal region was required, although not sufficient, for heat-shock tolerance and localization. Preliminary data suggests that chimeras complementing tcb3Δ heat-shock hypersensitivity also mediate ER peak formation.
Keywords: Biología molecular - Congresos; Abiotic stress; Synaptotagmin; Tricalbin; Contact site